Selective oxidation of tool steel surfaces under a protective gas atmosphere using inductive heat treatment - Schöler S. (MATEC Web of Conferences, 2018)
For the realization of liquid lubricant free forming processes different approaches are conceivable. The priority program 1676 “Dry forming - Sustainable production through dry machining in metal forming” addresses this issue in the context of metal forming processes. The present study reports results from one subproject of the priority program that employs selective oxidization of tool steel surfaces for the implementation of a dry sheet metal deep drawing process. Within the present study, specimen surfaces of the tool steel (1.2379) were heat-treated to optimize their tribological properties with respect to sliding wear behaviour in contact with drawn sheet metal (DP600+Z). The heat treatment was designed to result in the formation of selective oxide layers that can act as friction reducing separation layers. The heating setup employed an inductive heating under protective gas atmosphere. Selective oxidation was realized by controlling the residual oxygen content. Specifically, the specimens were heated in the near-surface region just above the annealing temperature, thus avoiding the degradation of mechanical properties in the bulk. Evaluation of hardness along cross-sections of each specimen revealed suitable initial temperatures for the inductive heat treatment. Oxide layer systems were analyzed regarding their tribological sliding wear behaviour after selective oxidation, as well as their morphology and chemical composition before and after the sliding wear tests.